Full spin switch effect for the superconducting current in a superconductor/ferromagnet thin film heterostructure - Leksin, Pavel V.; Garif’yanov, N. N.; Garifullin, I. A.; Schumann, J.; Vinzelberg, H.; Kataev, V.; Klingeler, Rüdiger; Schmidt, O. G.; Büchner, B. (Applied physics letters, 2010)
Using the spin switch design F1/F2/S theoretically proposed by Oh et al., [Appl. Phys. Lett. 71, 2376 (1997)], that comprises a ferromagnetic bilayer as a ferromagnetic component, and an ordinary superconductor as the second interface component, we have realized a full spin switch effect for the superconducting current. An experimental realization of this spin switch construction was achieved for the - CoO - 𝑥 - /Fe1/Cu/Fe2/In - CoOx/Fe1/Cu/Fe2/In - multilayer.
Gesehen am 13.03.2023